Nāsakh dalam Sunnah dan Implikasinya terhadap Hukum dan Tafsir Al-Qur’an - Udin Saprudin (Lembaga Yasin AlSys, 2026)
Although the concept of naskh (legal abrogation) has long been a focus in Islamic legal studies, research that specifically addresses the implications of naskh in the Sunnah for Islamic law (fiqh) and Qur’anic exegesis remains limited and fragmented. This study aimed to analyze the theoretical foundations of naskh in the Sunnah, evaluate its practical implications for legal istinbāṭ, and explore its hermeneutic impact on Qur’anic interpretation. The study employed a qualitative approach with a systematic literature review design, involving 131 scholarly works selected through a comprehensive search of academic databases (SciSpace, Google Scholar), which were then thematically analyzed to identify key debates, classifications, and methodological frameworks. Data were analyzed using content analysis and a comparative juridical method to synthesize classical and contemporary perspectives. The findings show that naskh in the Sunnah operates as a complex hermeneutic instrument with significant implications: (1) it influences the legal validity derived from hadith, (2) it generates methodological challenges in chronological verification, and (3) it shapes interpretive approaches to resolving textual contradictions. These findings contribute to the development of uṣūl al-fiqh methodology and broaden understanding of the Sunnah–Qur’an relationship in Islamic legal theory. The study concludes by emphasizing the importance of rigorous chronological-contextual analysis in validating naskh claims and encouraging contemporary jurists to adopt evidence-based and transparent abrogation methodologies. The implications include a theoretical contribution to the development of Islamic hermeneutics and practical implications for legal scholars, muftī, and educational institutions in formulating more nuanced approaches to textual interpretation, while also opening opportunities for further exploration of empirical case studies of hadith considered mansūkh and their contemporary juridical applications.